A Case of a Stafne Bone Defect Associated with Sublingual Glands in the Lingual Side of the Mandible - Kamichika Hayashi; Takeshi Onda; Takahiro Iwasaki; Mitsuru Takata; Kiyotaka Mori; Hiroyuki Matsuda; Shinya Watanabe; Hidetoshi Tamura; Takahiko Shibahara; Masayuki Takano (Case Reports in Dentistry)
A Stafne bone defect from the mandibular anterior to the premolar region is an extremely rare case. A case of a Stafne bone defect extending from the mandibular anterior to the premolar region was presented. Computed tomography (CT) and magnetic resonance imaging (MRI) suggested that salivary gland tissue connected to the sublingual glands was involved in the formation of the cavity. The patient was a 68-year-old man who was examined at our hospital’s emergency outpatient department after a traffic accident. He was referred to our department for the treatment of contusions of the lips and oral cavity. A bone defect in the lingual side of the mandible from the right anterior to the right premolar region was incidentally detected on CT. CT showed a rounded cavity in the lingual side of the mandible that had a lingual opening, was monocystic, and had a cortical margin. The margin of the cavity was relatively dull and regular. MRI showed that the tissue filling the cavity in the lingual side of the mandible had similar signal intensity as the sublingual glands and was contiguous with the normal sublingual glands. Based on these findings, the bone defect was diagnosed as a Stafne bone defect filled with salivary gland tissue connected to the sublingual gland tissue.